MODAL SOSIAL KELOMPOK BURU BABI DI NAGARI LIMO KAUM KABUPATEN TANAH DATAR PROVINSI SUMATERA BARAT - Pasta Handika. M; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research was conducted in Nagari Limo Kaum, Tanah Datar Regency, West Sumatra Province with the aim of knowing the traditional activities of hunting pigs in Nagari Limo Kaum and the social capital contained in the Limo Kaum pig hunting group. This research uses descriptive qualitative research method. Data collection through interview, observation, and documentation techniques. The results showed that the activity of hunting pigs went through three stages. The first stage before the activity was carried out by deliberation and inviting pig hunters. The implementation stage includes the peak of hunting for pigs in the forest, the process of bathing dogs in the river, hunters go to the hunting location until they wait for the game to start, start hunting activities, rest breaks to move hunting locations. The last stage is the post-hunting stage for pig hunters and the committee. The social capital found in the pig hunting group in Nagari Limo Kaum is the network that exists in the Limo Kaum pig hunting group, namely good relations between members and networks with outside parties to build cooperation to achieve the same goal. Trust itself is formed among fellow members of hunting pigs because of the same hobby and trust in helping in every activity carried out as well as trust from outside parties in helping in every activity. Values and norms are important things to be maintained by every member of the hog hunting because the norm is something that is not written and is obeyed by every member if they violate the agreed rules, they will get a warning in the form of a warning. Keywords: Social Capital, Pig Hunting Traditions, Pig Hunting Activities